The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1021/acs.joc.1c00273
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Dehydrosulfurative Carbon–Oxygen Cross-Coupling of 3,4-Dihydropyrimidine-2-thiones with Aryl Alcohols

Abstract: A Pd-catalyzed/Cu-mediated oxidative dehydrosulfurative carbon–oxygen cross-coupling reaction of 3,4-dihydropyrimidin-1H-2-thiones (DHPMs) with aryl alcohols is described. Due to the ready availability of diverse DHPMs and aryl alcohols, the reaction method offers facile access to biologically and pharmacologically valuable 2-aryloxypyrimidine derivatives with rapid diversification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 58 publications
(56 reference statements)
1
5
0
Order By: Relevance
“…This result supports that the oxidative dehydrogenation (aromatization) proceeds via a radical intermediate as described in the literatures published by others 15 and us. 11,13 The reaction of 2-mercaptopyrimidine 7 with phenol provided the phenoxypyrimidine 8 (Scheme 4B), which can agree with the proposition that the C-S single bond generated aer deprotonation participates in the coupling of DHPM. We found that the reaction of dihydropyrimidinyl thioether 9 with PhOH yielded pyrimidinyl thioether 10 as the major product along with a trace amount of 3a, which indicates that the oxidative dehydrogenation could proceed prior to the C-O coupling.…”
supporting
confidence: 69%
See 2 more Smart Citations
“…This result supports that the oxidative dehydrogenation (aromatization) proceeds via a radical intermediate as described in the literatures published by others 15 and us. 11,13 The reaction of 2-mercaptopyrimidine 7 with phenol provided the phenoxypyrimidine 8 (Scheme 4B), which can agree with the proposition that the C-S single bond generated aer deprotonation participates in the coupling of DHPM. We found that the reaction of dihydropyrimidinyl thioether 9 with PhOH yielded pyrimidinyl thioether 10 as the major product along with a trace amount of 3a, which indicates that the oxidative dehydrogenation could proceed prior to the C-O coupling.…”
supporting
confidence: 69%
“…With respect to base, Ag 2 CO 3 , which gave the desired product in 91% yield, was superior to other bases examined in the studies, such as Cs 2 CO 3 , K 2 CO 3 , t-BuOK, CsF, and Na 2 CO 3 (entries 8-12). Toluene was better than other solvents, such as o-xylene, 1,4-dioxane, N,N-dimethylformamide (DMF), N-methyl-2-pyrrolidone (NMP), or dimethylsulfoxide (DMSO) for the reaction (entries [13][14][15][16][17]. With respect to the amount of Cu(OAc) 2 , it was shown that 1.5 equivalents of Cu(OAc) 2 was as effective as 2 equivalents of Cu(OAc) 2 in the production of the desired product (entry 18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“… 21 As a result, we realized the Pd-catalyzed/Cu-mediated 2-arylation reaction of 1-Boc 2-methylthio-DPs with arylstannane reagents. 22 The Boc group significantly increases reactivity of DPs. This protocol enables the synthesis of 6-unsubstituted 2-aryl-DPs using various substituents at the 2- and 4-positions; to the best of our knowledge, the general formula of the 2-aryl-DPs has not been reported.…”
Section: Introductionmentioning
confidence: 97%
“…To our knowledge, no reports describing Cu-promoted direct C–N cross-coupling of thiono substrate with amine have been published. 18–20…”
mentioning
confidence: 99%